Adaptive reuse of carob warehouses in Northern Cyprus - Yüceer, Hülya; Vehbi, Beser Oktay (Open House International Association, 2014)
Scattered mainly along the coast of Cyprus, a series of modest stone built carob warehouses provide a historical legacy of the agricultural, social and economic life of the rural areas of Cyprus during the late 19th and early 20th century. They were constructed of local materials and employed local building techniques, and have become a largely unrecognized part of the local landscape. Most remain in a dilapidated condition through neglect and weathering throughout the years. It is suggested that this is largely due to a lack of understanding of their cultural significance, and a lack of vision as to how a holistic conservation approach could help to address wider strategic policy objectives in the areas of sustainable tourism/place marketing, and rural economic development. More specifically it is suggested that a tourism path incorporating former carob collecting routes could support the adaptive re-use of the former warehouses based upon contemporary cultural needs and opportunities. The development of such an approach will require a multiagency, cross-sectoral involvement that sees these buildings as a significant cultural resource.
Keywords: Adaptive re-use; Carob warehouse; Cultural heritage; Cultural tourism